Dental occlusal form and function in Equus capensis: evaluating a controvertible taxonomic status - Malherbe, Megan (Department of Archaeology, 2020)
The Giant Cape zebra Equus capensisis one of the most iconic fossil herbivore species of the South African Quaternary. It is widely believed to have persisted relatively unchanged in its morphology for the duration of its existence, that encompassed the mid-to late Pleistocene. Described as a large-bodied equid, its skeletal remains were originally regarded as distinct and readily distinguishable from those of other fossil equids, especially with respect to their large size. This applied particularly to its cheek teeth, that were described as large with unique occlusal enamel morphology. Palaeontologists have generally accepted the taxonomic status of E. capensis without question. However in reality, its taxonomic status is far from incontrovertible as many of its definitive morphological traits are based on conjecture. Equus capensis was originally described on the basis of a large mandible embedded in limestone that had much of its dental row obscured. The rest of it was reconstructed using unassociated, usually isolated osteological elements from a variety of localities. Perhaps not surprisingly, apart from size, researchers have struggled over the years to distinguish between E. capensis skeletal elements and those of other fossil equids. An ancient DNA study of four E. capensis teeth further compounded the uncertainty around its taxonomic status by exposing a high degree of genetic similarity to E. quagga. The present study represents the first systematic investigation of morphological traits originally used to define E. capensis. Specifically, it considers dental occlusal enamel form and function to help shed light on the taxonomic status of E. capensis. Geometric morphometrics was used to compare premolar and molar occlusal enamel pattern in E. capensis and a large comparative equid sample. This was followed by an evaluation of levels of enamel complexity. Next, traditional linear methods were used to compare overall occlusal dental form. Finally, meso wear analysis was used to evaluate dental function. Analyses of dental occlusal enamel form were able to distinguish E. capensis teeth from those of equids in the comparative sample on the basis of size, but not shape. This result is telling since the shape of dental occlusal enamel bands carries greater taxonomic significance than their size. Size is easily influenced by environmental factors and may fluctuate through time. Also, analyses of mesowear patterns were unable to separate E. capensis teeth from those of E. quagga, with which it is thought to have co-occurred. Overall the results of this study do not support the legitimacy of E. capensisas as a taxon and lays the ground for additional enquiries.